Johannine metaphors/symbols linked to the Paraclete-Spirit and their theological implications - Joubert, J. (Acta Theologica, 2007)
The Johannine author uses metaphors and symbols to enable the primary and secondary readers to come to a better understanding of the Paraclete-Spirit. The study of particular Johannine metaphors is valuable in understanding the message and theology of John. The use of the dove, water and wind metaphors in the Johannine Gospel definitely has functional and theological implications for the Pneumatology of John. The Johannine author uses imagery freely in expressing his Pneumatological message. He does not express his message regarding the Paraclete-Spirit merely in the form of a theological discourse, but by using the metaphors dove, water and wind. By exploring the relationship between the various Paraclete-Spirit metaphors, a larger and more coherent picture emerges, which opens the view to the interrelatedness of various theological themes. Such a metaphorical description of the Paraclete-Spirit in the Johannine Gospel has genuine potential and deserves to be explored.